Barriers to preexposure prophylaxis use among individuals with recently acquired HIV infection in Northern California. Issue 5 (4th May 2019) - Marcus, Julia L.; Hurley, Leo B.; Dentoni-Lasofsky, Dennis; Ellis, Courtney G.; Silverberg, Michael J.; Slome, Sally; Snowden, Jonathan M.; Volk, Jonathan E.
ABSTRACT: Barriers to HIV preexposure prophylaxis (PrEP) use have not been well-characterized in people who became HIV-infected, all of whom could have benefited from PrEP. We invited Kaiser Permanente Northern California members diagnosed with HIV during 2014–2016, following a negative HIV test in the prior year, to complete a survey assessing barriers to PrEP use before HIV diagnosis. Of 268 patients surveyed, 122 (46%) responded. Median age was 36, most (84%) were men who have sex with men, and 64% were of minority racial/ethnic background. Thirty-six (30%) had discussed PrEP with a provider, of whom 10 were diagnosed with HIV at PrEP intake. Overall, only 5 (4.1%) had used PrEP, and all 5 discontinued before diagnosis. Among all respondents, the most common barrier to PrEP use was lack of PrEP awareness (51%). Among those aware of PrEP, the most common barriers were cost/insurance concerns (36%) and perceived low risk for HIV (24%). Lack of PrEP awareness ranged from 39% among those aged 25–34 to 88% among those aged <25 ( P = 0.011), and from 33% among Hispanics to 69% among Blacks ( P = 0.055). Increasing awareness and affordability of PrEP, and facilitating accurate assessment of HIV risk, are critical to reducing missed opportunities for PrEP.